Assessment of Fungal Filtrates Efficiency against Escherichia coli in Comparison with Common Artificial Antibiotics - Nihad Habeeb Mutlag (Journal of Global Pharma Technology, 2018)
The study aim to isolate , identify and characterize the Escherichia coli and look for their antibiotics resistance in children with diarrhea in najaf , the study includes 60 samples of stools gathered from patients children visiting Educational AL_Zahraa hospital for the period beginning of November 2016 to mid-January of the same year, the age of these children were less than ten years , specimens were phenotypic assays , microscopically examined and diagnosed by biochemical tests , the highest bacterial pathogens isolated were Escherichia coli. The sensitivity of isolates of E.coli were examined for 11 types of antibiotics, E. coli exhibite different pattern of resistance to different antibiotics ,it is have highest resistance to penicillin (ampicillin and carbenicillin), and it is have higher resistance for ceftazidime and cefepime , while have moderate resistance for aztreonam.it is have lowest resistant rate to imipenem ,meropenem and ertapenem.Also the same isolates of E.coli were examined by the Pleurotus ostreatus fungi filterates which appeare a significant values in the inhibition of growth of E.coli in petri dish which reach 8 cm in compare with antibiotics that used in the study .